The influence of grapes production and consumption on the price in Romania - Maria Nica (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
In this paper, it is desirable to determine the influence of production and consumption of grapes on the price in Romania. In order to determine this influence, the areas cultivated with grapes, the production of grapes, as well as their consumption in the last years, will be analyzed. With the help of the National Institute of Statistics website data on average grape prices, annual price differences as well as the difference between the price of table grapes and the price of wine grapes can be ascertained. With this data as well as the correlation coefficient, it will be possible to determine the influence of the production and consumption of grapes on the price of this food.
Keywords: Q11; 330; consumption; grape prices; table grapes; wine grapes